2021
DOI: 10.1002/adsc.202001456
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polysubstituted Phenols by Rhodium‐Catalyzed C−H/Diazo Coupling and Tandem Annulation

Abstract: The rhodium(III)-catalyzed CÀ H/diazo coupling and tandem annulation of 3-oxopent-4enenitriles have been proposed for the synthesis of polysubstituted phenols. Most products of phenols are obtained in good yields. Several preliminary mechanistic studies and derivatization reactions of phenol products were also performed. This method offers an alternative approach for the synthesis of useful diverse phenols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…oxopent-4-enenitriles with α-diazocarbonyl compounds (Scheme 25c). [71] The methodology being the first example of its kind requires easily accessible and cost-effective substrates where the directing group acts as a part of the cyclization process, thereby generating tetra-and penta-substituted phenols in one step.…”
Section: R E C O R D R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…oxopent-4-enenitriles with α-diazocarbonyl compounds (Scheme 25c). [71] The methodology being the first example of its kind requires easily accessible and cost-effective substrates where the directing group acts as a part of the cyclization process, thereby generating tetra-and penta-substituted phenols in one step.…”
Section: R E C O R D R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…Based on the above mechanism research experiments and referring literatures, [14][15][16] a possible mechanism is thereby proposed (Scheme 4). At the beginning, the depolymerization product of [Cp*RhCl 2 ] 2 is likely to be treated by -OAc to generate the active catalyst Cp*Rh(OAc) 2 .…”
Section: Scheme 3 the Mechanism Research Experimentsmentioning
confidence: 99%
“…Previously, we developed 3‐oxopent‐4‐enenitriles and sequentially achieved their rhodium(III)‐catalyzed C—H bond activation and annulation with diazo compounds leading to polysubstituted phenols, which also underwent the C—C/C—C coupling pathway (Scheme 1a). [ 16 ] As a continuation of our ongoing exploration on metal catalyzed reactions and the construction of heterocycles, [ 17 ] and based on recent reports on chelation‐assisted alkenyl C—H functionalization, [ 18 ] we herein seek to investigate the reaction profile of 3‐oxopent‐4‐enenitriles with alkynes under rhodium catalysis. The experimental results showed that polysubstituted 2 H ‐pyran derivatives were displayed through regioselective C—O and C—C bonds formation originating from O—Rh bond coupling (Scheme 1b).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In addition, other methods mainly involve basic reactions, which include benzannulation, 8 Diels–Alder cycloaromatization, 9 cyclocondensation of enones with 1,3-dicabonyl compounds 10 and others. 11 Although great progress has been made in the synthesis of phenols, a number of notable limitations exist: introducing additional directing groups, requiring transition-metal catalysis, focusing on special functional substrates, or the synthesis of multi-substituted phenols being difficult, particularly heterocycle-fused phenols. Therefore, the development of efficient and straightforward strategies for functionalized phenol construction is still a desirable and challenging issue.…”
Section: Introductionmentioning
confidence: 99%